IMPLEMENTASI UNDANG-UNDANG NO. 14 TAHUN 2005 SEBAGAI DASAR HUKUM PADA ETOS KERJA GURU DALAM PENGEMBANGAN KARIER - Eko Budiywono; Muhammad Rifqi Sovitunnizar (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
This researching aims to search the correlation of teacher’s work ethos with career development, where this research is correlational type to look for how the correlation between the two variables. The population in this researcing amounted to 34 people and the sampling technique used is a total census, so that a total of 34 teachers as respondents were sampled. The data analysis technique used is descriptive statistical analysis and product moment correlational analysis. This researching find that the correlation between career development with teacher’s work ethos is get 0.769. This result shows that there is a positive and significant correlation between teacher’s work ethos with career development of Darusalam Blokagung Senior High School included strong categories.